Rhizobial plasmid pLPU83a is able to switch between different transfer machineries depending on its genomic background - Torres Tejerizo, Gonzalo Arturo (2014)
Plasmids have played a major role in bacterial evolution, mainly by theircapacity to perform horizontal gene transfer (HGT). Their conjugative transfer(CT) properties are usually described in terms of the plasmid itself. In thiswork, we analyzed structural and functional aspects of the CT of pLPU83a, anaccessory replicon fromRhizobiumsp. LPU83, able to transfer from its parentalstrain, fromEnsifer meliloti, or fromRhizobium etli. pLPU83a contains a com-plete set of transfer genes, featuring a particular organization, shared with onlytwo other rhizobial plasmids. These plasmids contain a TraR quorum-sensing(QS) transcriptional regulator, but lack an acyl-homoserine lactone (AHL) syn-thase gene. We also determined that the ability of pLPU83a to transfer fromR. etliCFN42 genomic background was mainly achieved through mobilization,employing the machinery of the endogenous plasmid pRetCFN42a, fallingunder control of the QS regulators from pRetCFN42a. In contrast, from itsnative or from theE. melilotibackground, pLPU83a utilized its own machineryfor conjugation, requiring the plasmid-encodedtraR.Activation of TraRseemed to be AHL independent. The results obtained indicate that the CT phe-notype of a plasmid is dictated not only by the genes it carries, but by theirinteraction with its genomic context.